Upaya Guru Pendidikan Agama Islam dalam Meningkatkan Prestasi Belajar Siswa di MTs Swasta Darul Ulum Lhokseumawe - Nuruzzahri, Nuruzzahri (Tematik: Jurnal Penelitian Pendidikan Dasar, 2025)
This study investigates the efforts of Islamic Religious Education (PAI) teachers in enhancing student academic achievement and examines whether these efforts contribute to improved learning outcomes. Conducted at MTs Swasta  Darul Ulum North Bekasi from October 2023 to December 2024, the research adopts a qualitative approach to explore the relationship between teacher interventions and student performance. The study identifies several strategies employed by PAI teachers, including the use of contextually appropriate and engaging teaching methods, the integration of inspirational stories from prophets and companions, academic guidance and counseling, the application of the Merdeka curriculum, enrichment activities, targeted remediation, regular assignments, and monthly assessments. Findings reveal that while the improvement in student achievement is gradual and not drastically significant, the consistent and diverse efforts of PAI teachers in Grade 8 contribute positively to learning outcomes. The study concludes that sustained pedagogical interventions, rooted in both motivational and academic support, can progressively enhance student performance in Islamic education.